O zumbi como personagem midiático: desdobramentos políticos - Oliveira, André (2012)
Zombies have been part of people s imagination for many centuries. However, for the last twenty years, a zombie culture has been developed and it has been taking its place throughout different types of media, such as audiovisual and press. Moreover, this culture has also been present in people´s celebrations and manifestations, for example: festivals, parties, performances, etc. The purpose of this dissertation is to identify how the new versions of zombies constitute not only a form of entertainment, but also a political metaphor, representing the disqualification of human life (bare life) and the fine line between life and death. This research comprises from the pioneer movie Night Of The Living Dead (1968), directed by filmmaker George Romero, to recent work related to films, comic books, photographs and images found online. The methodology brings together bibliographical research and the analysis of images which were selected from diverse media. The theoretical context is formed by the political studies of the fictional genre, which are based on body horror, proposed by Benjamin Noys (2005), and the analysis of Auschwitz Living Dead, known as Muselmann and transformed into one of the important paradigms of contemporary political philosophy by Giorgio Agamben (2008). The study of the way man s natural life influences power mechanisms will be carried in the field of communication throughout the corpomidia theory (KATZ & GREINER, 2005). The expected result is the questioning and discussion of the apathy that is brought by zombies, which characterizes some of the fundamental dimensions of current social behavior in society and in the media